1990
DOI: 10.1071/ch9900825
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Pyrrolic Compounds. LXIII. Synthetic Studies of Petroporphyrins With Fused Six-Membered Ring Systems

Abstract: Several approaches to the synthesis of porphyrins bearing fused six- membered ring systems were explored with the aim of obtaining the petroporphyrin (4a). This was ultimately achieved by an intramolecular cyclization of a porphyrin with a propanoyl chloride side chain in the presence of stannic chloride. Methylation of the intermediate ketone with CH3Li and reduction of the resultant alcohol with NaBH3CN/Znl2 furnished (4a).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These molecules have been most popular for their use in the synthesis of porphyrins, chlorins, , and tetrahydrocorrins. , The 1,19-dimethyl-derivatives, sometimes formed in situ, have also been used to synthesize metalloporphyrins by cyclization in the presence of metal ions. From the earliest of these metal cyclization reactions it was discovered that bilene- b analogues form homoleptic metal complexes . This work was extended to investigate the metal-complex geometries of dipyrrins through a study upon bilene- b metal complexes such as compound 72 : it was shown that they displayed complexation behavior similar to that of 1,9-sterically hindered dipyrrins (Figure ). ,
72 Structure of a zinc(II) bilene- b complex.
…”
Section: 5 Bilene-b Complexesmentioning
confidence: 99%
“…These molecules have been most popular for their use in the synthesis of porphyrins, chlorins, , and tetrahydrocorrins. , The 1,19-dimethyl-derivatives, sometimes formed in situ, have also been used to synthesize metalloporphyrins by cyclization in the presence of metal ions. From the earliest of these metal cyclization reactions it was discovered that bilene- b analogues form homoleptic metal complexes . This work was extended to investigate the metal-complex geometries of dipyrrins through a study upon bilene- b metal complexes such as compound 72 : it was shown that they displayed complexation behavior similar to that of 1,9-sterically hindered dipyrrins (Figure ). ,
72 Structure of a zinc(II) bilene- b complex.
…”
Section: 5 Bilene-b Complexesmentioning
confidence: 99%